(untitled) (Research, Society and Development, 2021)
The aimed of the study was to evaluate the caloric value as a function of the proximal composition and correlate the selling price with the nutritional values ​​of commercial cuts of tambaqui (Colossoma macropomum) and pirarucu (Arapaima gigas) in different weight classes. The sample collections were performed in two processing units located in the state of Rondônia, Brazil. Were 200 tambaquis in five weight classes were studied. And, were 77 pirarucus were studied in seven weight classes. The design was completely randomized, with processing carried out in triplicate. The Kruskal-Wallis test (α=0.05) was used to compare the averages and the Spearman correlation (ρ) between price and nutrients. The commercial cuts with the highest caloric value were the tambaqui filet (145.70 kcal/100g) and the pirarucu filet mignon (119.11 kcal/100g) (p<0.05). And the less caloric commercial cuts were steak of tambaqui (100.47 kcal/100g) and pirarucu loin 102.01 kcal/100g) (p<0.05). It was also observed that the variables caloric value and protein content did not correlate with the price of the kilo of fish for the different commercial cuts, which leads to infer that, possibly, the sensorial, market and cultural factors were responsible for the price variations. Regarding the caloric value according to the composition of the tambaqui, the Class 4 was the most efficient category for production and commercialization. And in the composition of the pirarucu, the Class 4 presented satisfactory values of proteins and lipids and a good percentage of mineral matter.